TIPS-Ethynylated naphthodiquinoline and naphthodiacridine: novel diazabisacenes - Ahrens, Lukas; Maier, Steffen; Misselwitz, Erik; Oeser, Thomas; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
The synthesis of two diazabisacenes is reported. A bisboronated naphthalene was Suzuki-coupled to substituted ethyl nicotinates, then cyclized by intramolecular Friedel-Crafts acylation. The resulting diketones were alkynylated and reduced to give the title compounds, bis(TIPS-ethynyl)-substituted naphtha[1,8-gh:5,4-g′h′]diquinoline and naphtho[1,8-bc:5,4-b′c′]diacridine. Nitrogen incorporation stabilizes the bisacenes with respect to oxidation compared to their consanguine nonaza analogs.